Infrastructure Coverage and the Poor : The Global Perspective - Komives, Kristin (World Bank, Washington, DC, 2014)
The authors use the World Bank's Living Standards Measurement Study (LSMS) surveys from 15 countries (covering more than 55,500 households) to examine the relationship between infrastructure coverage and household income. The results show that throughout the world all income groups have much higher levels of coverage for electricity than for other formal infrastructure services (in-house piped water service, sewerage service, and private telephone service). In many countries most households in urban areas now have electricity service. As monthly household incomes increase from $100 to $250, coverage of all these infrastructure services rises, but at different rates. The findings confirm that the very poor rarely have these infrastructure services - with exceptions. The very poor often do have electricity if they live in urban areas. The very poor in Eastern Europe and Central Asia have much higher levels of coverage than those elsewhere in the world; they often have electricity, water, sewer, and telephone services. The results also suggest that if the poor gain access to services in their communities, many will decide to connect.